Epidemiology of uterine myomas and clinical practice in Spain: An observational study. (July 2018) - Monleón, Javier; Cañete, María Luisa; Caballero, Virginia; del Campo, Manuel; Doménech, Alejandro; Losada, Miguel Ángel; Calaf, Joaquim; ,
Abstract: Objective: Characterization of the clinical features of symptomatic uterine myomas in Spanish women visiting the gynaecologist, including impact on quality of life and possible risk factors, description of main therapeutic approaches, and evaluation of symptom and quality of life progression 6 months after inclusion in the study. Study design: This was an observational, epidemiological, non-interventional, multicentre study performed between June 2015 and March 2016. Data were collected at baseline and follow-up visits 6 months apart from women with a diagnosis of uterine myomas and visiting a participating gynaecologist in outpatient units of private clinics or public hospitals in Spain. Data consisted of a gynaecological clinical inspection, an interview with open questions to the patients, and self-administered generic questionnaires. The main outcome measures were socio-demographic data, clinical history, myoma clinical features, symptomatology, data on surgical choices, patient satisfaction, and risk factors associated to myomas. Results: Data were collected from 569 patients (1, 022 myomas) at 56 hospitals and private gynaecological offices in Spain. Most patients (85%) presented between 1 and 3 myomas, predominantly intramural and subserosal. Most common symptoms reported heavy menstrual bleeding and pelvic pain, and the mean (±SD) symptom severity score in the UFS-QoL questionnaire (range 0–100) was 50.89 ± 20.85. Up to 60.5% of patients had an indication of surgery (55.8% myomectomies, 40.4% hysterectomies) to treat their uterine myomas and 39.5% followed other therapies, mainly pharmacological. After six months of treatment, all patients had experienced significant reduction in symptoms and improvement of quality of life. Conclusions: The most frequent symptoms reported by women diagnosed with uterine myomas were heavy menstrual bleeding, pelvic or abdominal pain and dysmenorrhea; QoL was impaired reflecting high symptom distress. We found that surgery was the main therapeutic approach to manage uterine myomas in Spain. Both surgical and non-surgical treatments achieve relevant improvements in symptom severity and quality of life.